PENGARUH KINERJA LINGKUNGAN DAN KARAKTERISTIK PERUSAHAAN TERHADAP CORPORATE SOCIAL RESPONSIBILITY (CSR) DISCLOSURE (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI) - Permana, Virgiwan Aditya; Rahardja, Rahardja (Diponegoro Journal of Accounting, 2012)
The aim of this research was to examine the effect of environmental performance and corporate characteristic toward corporate social responsibility (CSR) disclosure of manufacturing company. The environmental performance was measured by the company performance in PROPER (Program Penilaian Peringkat Kinerja Perusahaan dalam Pengelolaan Lingkungan Hidup). This research attampts to used five corporate characteristic, they are company size, profitability, profile, size of board commissioner and leverage. Dependent variable used in this research was CSR disclosure. The population of this research is all the manufacturing company listed in Indonesia Stock Exchange during 2008-2010. The total sample of this research was 159 companies. The collection of research data used purposive sampling method. The data analysis method used is analysis regression and descriptive statistics. The result showed that environmental performance, profitability, company size, and profile significantly influence to CSR disclosure. Meanwhile, size of board commissioner and leverage has no significant impact toward CSR disclosure.